Driving mechanisms of high-quality development in China’s sports industry - Huang, Mingzhe; Liu, Feiping; Liu, Tengsheng (Transformations In Business & Economics, 2026)
This study investigates the factors and policy measures that condition the high-quality progress of China’s sports economy , underpinned by the New Structural Economics approach. While there have been advancements in the sector, there are still issues such as regional imbalance, insufficient skills in the workforce, and inadequate integration with other sectors, notably tourism and technology. Six hypotheses encompassing policy support, infrastructure, human capital, technological innovation, market stimulation, and industrial structure were empirically tested using data were collected from 200 athletes, coaches, and policymakers. Descriptive statistics show that policy support (mean=4.161) and policy-market synergy (mean=4.083) received the highest mean ratings, while industrial integration received the lowest (mean=3 .649). Correlation analysis confirmed that infrastructure investment (r=0.463) showed the strongest association with high-quality development, followed by technological innovation (r=0.445) and human capital development (r=0.412). Path analysis had likewise shown that policy measures (P=0.421 , p<0.001) and technical innovation (P=0.367 , p=0.001) had the highest direct impact, while market demand (P=0.238 , p=0.012) had a moderate impact. ln conclusion, as recommended by the findings, integrated policy tracks , technology , and infrastructure are critical points to improve the overall sports economy towards sustainability and inclusion. The findings provide important policy and managerial implications by emphasizing the critical role of policy support, technological innovation, and infrastructure development in driving high-quality growth. It is recommended that policymakers prioritize coordinated policy-market mechanisms and targeted investments in innovation and human capital, while managers focus on improving resource allocation and operational efficiency to achieve sustainable and inclusive development in the sports industry.